Engineering Interfaces in Polymer Nanocomposites for Self-Healing Applications - Gupta, Ranjeetkumar (Cranfield University, 2017)
3MT presented at the 2017 Defence and Security Doctoral Symposium.Polymer nanocomposites (PNCs) are finding various applications and its obvious since nanocomposites for example can effectively couple the flexibility of polymer and high strength of carbon, thus offering the combination of highest performance and processibility. Though the uniform dispersion of nanoparticles in the polymer is the biggest challenge. And unless achieved so, the nanocomposite won’t serve the useful properties as desired of it. This eventually relates to the issue involving large interfaces formed by the included nanoparticles. The proposed research work deals with the critical aspect of controlling the interfacial structure-property-functions relationships, by functionalisation of nanoparticles for controlling their interfaces and forming hierarchical networks with designed dispersion techniques for dictated positioning of nanoparticles. Thus, reducing total cost and weight of parts, with autonomous damage detection and self-healing characteristics; by engineering the interfaces accordingly. The autonomic self-healability triumphs even in the problematic cases where damage, or its site is hard to identify or even inaccessible. Specifically, such PNCs can be designed as insulating/conducting fabric/layer, electromagnetic-shielding, microwave absorption, corrosion & fire retardants, refractive index tuned optical fibres, and the list can be extended indefinitely. Popularity of PNCs are increasing in applications for micro UAVs, armours/liners, composite jet-vanes, wings and propellers for LCA, etc.
Keywords: 'Self-healing'; 'Polymer Nanocomposite'; 'Composite Structures'; 'DSDS17 3MT'; 'DSDS17'; 'Nanomaterials'; 'Composite and Hybrid Materials'